Reliability assessment of ultra-short gate length AlGaN/GaN HEMTs on Si substrate by on-state step stress. (September 2016) - Lakhdhar, H.; Labat, N.; Curutchet, A.; Defrance, N.; Lesecq, M.; De Jaeger, J.-C.; Malbert, N.
Abstract: Step-stress experiments are performed to investigate reliability assessment of ultra-short gate AlGaN/GaN high electron mobility transistor (HEMT) on Si substrate. A methodology based on a sequence of step stress tests has been defined for in-situ diagnosis of permanent degradation. The same stress conditions were applied on HEMTs with different geometries. It is found no evolution of the drain current during non stressful steps. The value of the critical degradation voltage beyond which the stress drain current starts to decrease significantly is also found dependent on the stress bias conditions, the gate-drain distance and the gate length.